A government value compensation model of waste recycling in an industrial park: A game theory approach. (1st December 2020) - Jin, Youliang; Tang, Zheng; Zhou, Qiong; Zeng, Huixiang; Mo, Shaowan
Abstract: This study establishes a game model of government value compensation for different types of industrial waste recycling in industrial parks and examines the standards for recycling firm waste based on maximizing government benefits. The impact factors of waste recycling, the government decision-making process regarding value compensation, and the firm waste-recycling decisions are evaluated, and a case study is conducted for model verification. The results show the following: the value compensation standard of the government increases with increasing waste-recycling cost and environmental benefits and decreases with decreasing waste disposal and raw material costs; a comparison of the equilibrium results of the government decision-making process on internal recycling indicates that the government value compensation strategy involving interfirm collaborative processing is better than centralized processing in industrial parks; government value compensation improves the reuse of firm waste and ensures more economic and environmental benefits. Highlights: Established a government compensation game model for industrial parks. The compensation policy was analyzed under different waste recycling models. Introducing Hunan NingXiang industrial park of China and giving a case study.